Pengembangan Media Pembelajaran Video dan Game Online Materi Kegiatan Ekonomi untuk Siswa Kelas 4 Sekolah Dasar - Riski, Ananda Novita; Airlanda, Gamaliel Septian (Universitas Nusantara PGRI Kediri, 2023)
This study aims to develop video learning media and online games for grade 4 elementary school students on economic activity material and to determine the feasibility level of the developed media. This type of research is research and development or Research and Development (R&D). The results of the preliminary study state that the media used by the teacher in learning is monotonous so that learning becomes less effective and students easily get bored. Media developed using the Borg & Gall model include 1) Research and development of initial information, 2) Planning, 3) Development of initial product drafts, 4) Initial trials, and 5) Product revision. The results of the study were conducted on 4th grade students at SD Negeri 3 Kaloran, totaling 11 people, obtaining a percentage of 90.54% in video media while online game media obtained a percentage of 91.63% with the second criterion of